Digital competence of the university student in times of COVID-19 - Jara Nunayalle, Jadira del Rocío (2022)
Background: In times of covid 19, digital competence provides various skills to students such as faster, more efficient and practical information search, which generates greater ease and accessibility to different sources for a better method of learning acquisition with new literacies. Objective of the study : The objective of the research was to compare the digital competence of university students from two universities in Lima. Method:It was a quantitative, non-experimental, cross-sectional study; A sample made up of 466 students (75% women and 25% men) from two fifth-cycle private universities in Lima aged between 21 and 28 years, selected under an intentional non-probabilistic sampling, was used. Results: It was observed that, of 233 students from private university 1, in terms of digital skills, 38.2% obtained a low level; 60.1% obtained medium level and 1.7%, high level and, in relation to private university 2, 9.4% obtained low level; 72.1%, medium level and 18.5%, high level. There are significant differences in the level of digital skills in students from two private universities since the level of significance calculated is p < .05 and the Mann Whitney U is 12156,000. Conclusion:In times of covid 19, digital skills are of great importance; therefore, they are present in university curricula since they allow students to develop new cognitive abilities and innovative skills that will be useful in their academic lives.